OPPORTUNITY PENDIDIKAN: TRANSFORMASI DI ERA DISRUPSI DAN REVOLUSI INDUSTRI 4.0 - Duryat, Masduki (Gema Wiralodra, 2019)
ABSTRACT Disruption is an innovation. This is an innovation that will replace the entire old system with new ways. Disruption has the potential to replace old players with new ones. Disruption replaces old technology with digital technology that produces something completely new and more efficient and more useful. Whereas in the Industrial 4.0 era, machines and factories will be connected, exchange data, work together, and make independent decisions collectively. The Industrial Age 4.0 offers time and resource efficiency, cost savings, increased income, agility, and innovation for the industry. The old industry or incumbent will be replaced by a more efficient new-style industry. Therefore this disruption must be anticipated so that we can see new opportunities in the future. In the context of education—especially high education— as a printer of skilled human resources—must be prepared with 4 C skills (creativity, critical thinking, communication and collaboration) must be thoroughly prepared because in this sophisticated era humans will co-exist with smart machines at workplace. Education must change, if not, then in 30 years we will face a big problem. Everything we teach should be different from machines — everything that is taught must make humans different from machines. Humans as products of education, must still have ethics/morals—because religion is truly a source of value/ethics—which must be implemented through education (Islam) in this disruption era.